A 99mTc‐tricine‐HYNIC‐labeled peptide targeting the neurotensin receptor for single‐photon imaging in malignant tumors. (7th January 2014) - Erfani, Mostafa; Zarrabi Ahrabi, Nakisa; Shafiei, Mohammad; Shirmardi, Seyed Pezhman
<x xml:space="preserve">Abstract</x> In this study, a new neurotensin (NT) analog was labeled with 99mTc via HYNIC chelator and tricine as coligand and investigated further. An NT (7–13) analog was prepared, and labeling with 99mTc was performed. The internalization rate and biodistribution of radiopeptide were studied in HT‐29 cells and nude mice bearing tumor, respectively. Radiolabeling with 99mTc was performed at high specific activities (54 MBq/nmol) with an acceptable labeling yield (>95%). In vitro cell line studies showed a specific internalization uptake up to 13.23 ± 0.45% during 4 h which was blocked in the presence of excess cold peptide to 0.83 ± 0.15%. In biodistribution studies, uptake was observed in NT receptor‐positive organs so that after 1 h the uptakes in mouse intestine and tumor were 1.23 ± 0.16% ID/g and 1.12 ± 0.11% ID/g, respectively. In animals co‐injected with excess cold peptide, reduction uptake in tumor and intestines were 73% (1.10% vs. 0.29% ID/g at 4 h) and 61% (1.22% vs. 0.47% ID/g at 4 h) respectively. Predominant renal excretion pathway with a highest accumulation of activity in bladder was observed for this radiopeptide. This radiolabeled peptide could be a candidate for detection of NT positive tumors.